Three-layer microfibrous peripheral nerve guide conduit composed of elastin-laminin mimetic artificial protein and poly(L-lactic acid) - Kakinoki, Sachiro; Nakayama, Midori; Moritan, Toshiyuki; Yamaoka, Tetsuji (Frontiers in Chemistry, 2014)
We developed a microfibrous poly(L-lactic acid) (PLLA) nerve conduit with a three-layered structure to simultaneously enhance nerve regeneration and prevent adhesion of surrounding tissue. The inner layer was composed of PLLA microfiber containing 25% elastin-laminin mimetic protein (AG73-(VPGIG)30) that promotes neurite outgrowth. The thickest middle layer was constructed of pure PLLA microfibers that impart the large mechanical stremgth to the conduit. A 10% poly(ethylene glycol) was added to the outer layer to prevent the adhesion with the surrounding tissue. The AG73-(VPGIG)30 composisting of an elastin-like repetitive sequence (VPGIG)30 and a laminin-derived sequence (RKRLQVQLSIRT: AG73) was biosynthesized using Escherichia coli. The PLLA microfibrous conduits were fabricated using an electrospinning procedure. AG73-(VPGIG)30 was successfully mixed in the PLLA microfibers, and the PLLA/AG73-(VPGIG)30 microfibers were stable under physiological conditions. The PLLA/AG73-(VPGIG)30 microfibers enhanced adhesion and neurite outgrowth of PC12 cells. The electrospun microfibrous conduit with a three-layered structure was implanted for bridging a 2.0-cm gap in the tibial nerve of a rabbit. Two months after implantation, no adhesion of surrounding tissue was observed, and the action potential was slightly improved in the nerve conduit with the PLLA/AG73-(VPGIG)30 inner layer.